Beyond alcohol oxidase: the methylotrophic yeast Komagataella phaffii utilizes methanol also with its native alcohol dehydrogenase Adh2. Issue 2 (18th February 2021) - Zavec, Domen; Troyer, Christina; Maresch, Daniel; Altmann, Friedrich; Hann, Stephan; Gasser, Brigitte; Mattanovich, Diethard
ABSTRACT: Methylotrophic yeasts are considered to use alcohol oxidases to assimilate methanol, different to bacteria which employ alcohol dehydrogenases with better energy conservation. The yeast Komagataella phaffii carries two genes coding for alcohol oxidase, AOX1 and AOX2 . The deletion of the AOX1 leads to the Mut S phenotype and the deletion of AOX1 and AOX2 to the Mut – phenotype. The Mut – phenotype is commonly regarded as unable to utilize methanol. In contrast to the literature, we found that the Mut – strain can consume methanol. This ability was based on the promiscuous activity of alcohol dehydrogenase Adh2, an enzyme ubiquitously found in yeast and normally responsible for ethanol consumption and production. Using 13 C labeled methanol as substrate we could show that to the largest part methanol is dissimilated to CO2 and a small part is incorporated into metabolites, the biomass, and the secreted recombinant protein. Overexpression of the ADH2 gene in K. phaffii Mut – increased both the specific methanol uptake rate and recombinant protein production, even though the strain was still unable to grow. These findings imply that thermodynamic and kinetic constraints of the dehydrogenase reaction facilitated the evolution towards alcohol oxidase-based methanol metabolism in yeast. Abstract : To consume methanol, yeasts employ methanol oxidases, while bacteria use more energy efficient methanol dehydrogenases, and we show that dehydrogenase is a hidden layer of methanol consumption also in the yeast Komagataella phaffii .